p) 2x-1=-3+x+4 q) 3x-2-2x-3=0 r) 10-9x+2x=2-3x s) 4x-4-5x=-6+90 t) 2-3x=-2x+12-3x
Soluções para a tarefa
Respondido por
2
Resposta explicação passo-a-passo:
(p) 2x - 1 = -3 + x + 4
2x - x = - 3 + 4 + 1
x = 2
(q) 3x - 2 - 2x - 3 = 0
3x - 2x = 2 + 3
x = 5
(r) 10 - 9x + 2x = 2 - 3x
- 9x + 2x + 3x = 2 - 10
- 4x = - 8
x = = 2
(s) 4x - 4 - 5x = - 6 + 90
4x - 5x = -6 + 90 + 4
- x = 88
x = - 88
(t) 2 - 3x = - 2x + 12 - 3x
- 3x + 2x + 3x = 12 - 2
2x = 10
x = = 5
estefanilorraine340:
obrigada
Respondido por
1
Resposta:
P) 2
Q) 5
R) 2
S) -88
T) 5
Explicação passo-a-passo:
fiquei com um pouco de duvida na S, mas o resto esta certo
Perguntas interessantes